Agility Path Through Work Values in Knowledge-Based Organizations: A Study of Virtual Universities - Yashar, Salamzadeh; Ajibisheh, Mehran Nejati; Aidin, Salamzadeh (Universidad Nacional de Colombia, 2014)
All people enter organizations with a formed personality and some initial experiences and values depending on the culture, which will, in turn, influence their efficiency and performance. Therefore, great attention must be paid to work values of the employees and the issues which affect them, especially in organizations that are complex in their structure and culture. Today’s dynamic environment requires organizations to be agile in their processes, with the issue being even more critical in knowledge-based organizations such as virtual universities. In this research, we identify the path through which organizations can achieve agility by means of work values. Although there are many dimensions in work values and organizational agility, using the methodology applied in this research, we omit some of these dimensions and find the best methods that will enable managers to wisely invest in the most important issues and get the best results in the path to achieve agility through work values.